Combining abilities analysis for ear rot resistance in popcorn hybrids development - Nunes de Almeida, Rafael; Vivas, Marcelo; Rosa dos Santos Junior, Divino; Gradice Saluci, Júlio Cesar; Cazadini Carlos, Mayara; Saltires Santos, Juliana; Teixeira do Amaral Júnior, Antônio; Scapim, Carlos Alberto (Revista Ceres, 2025)
Ear rot caused by fungi of genus Fusarium (FER) is one of the potentially harmful diseases to grain quality in maize. Given the capacity to produce mycotoxins, FER presents a risk to food safety. This study sought to identify parents and indicate hybrids of popcorn with a higher level of resistance to the incidence and severity of FER. Hybrids were produced from the crossing of 15 lines in S7 generation and 5 testers. The hybrids, together with the parents and five more genotypes used as control, were evaluated in a field trial. It was used a randomized block design arranged in 10 x 10 lattice. Data were submitted to analysis of variance by the F test (p < 0.05) and then by the mean grouping test of Scott Knott (p < 0.05). The results showed the possible to explore new sources of resistance to FER among germplasm evaluated. Both additive and non-additive gene effects are important in FER resistance. To obtain gains in FER resistance, the development of popcorn hybrids should consider the use of parental lines with low means of severity and good general combining ability